Empowerment and Accompaniment Poor Society With Disability Through Business Skill Of DeCoupage And Dried Flower Craft Rustic Style Decor - Shofia Hattarina; Nurul Saila; Firli Maulidiana; Maulidia Khoiry; Siti Fatimah (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
Based on data from Jawa Pos Radar Bromo writes the total poverty rate in Probolinggo Regency is around 18 percent. Therefore, it’s necessary to empower people with disabilities in Proboolinggo Regency to improve economic welfare. This empowerment is carried out by providing useful assistance and training for them, as well as the researchers involved in the research process. The place for the implementation of this mentoring and training in Paiton village and it will be held for 4 days, on October 27, 2021, which includes: Preparation of empowerment and mentoring programs with stakeholders. Decoupage business skills training and dried flower crafts. Product marketing training through online media. the follow-up to empowerment activities is mentoring to the point where they receive orders, goods pack and delivers. Furthermore the factors that encourage the success of empowering people with disabilities in Probolinggo Regency are the attitude of openness to others, as well as the support and participation of all stakeholders. The inhibiting factor is attitude and dependence. So far, people with disabilities in Probolinggo district often receive assistance from outside the consumptive sector. This causes people to be less independent and lead to dependence on others.